The utilization of sodium lignosulphonate extracted from Egyptian rice straw in leather tanning process - Nasr, Ahmed Ibrahim; Taha, Mohamed Gaber; Yosef, Hany Y; El-Shaer, Mohamed A (Majalah Kulit, Karet, dan Plastik, 2017)
Massive quantities of rice straw are burned annually in Egypt and caused environmental hazards. The present study investigated the utilization of rice straw to produce sodium lignosulphonate (SLS) as a water-soluble derivative of lignin in leather tanning and evaluate its usage as a tanning or re-tanning material as well as its effect on leather quality. The results of testing SLS as a leather tanning agent were unsatisfactory due to its slight effect on shrinkage temperature of leathers, unlike its use as a re-tanning material. Four concentrations of SLS (0%, 5%, 10%, and 20%) were used in re-tanning forty of sheep wet-blues. The results showed that using SLS as a re-tanning agent with concentration till 10% from pelts weight enhances some organoleptic properties, such as fullness and general appearance together with slight improvement in physical properties of leathers. Moreover, the addition of SLS with concentration 20% led to an excessive swelling in the collagen fibers as shown from depicted scanning electron micrographs and decreased trends of physical properties.